Scrutinising public land release: an investigation into the advantages of long-term leasehold arrangements in the delivery of well-located affordable housing - Van Rooyen, Raevaldo EJ (Centre for Law and Society, 2026)
Thirty years after the ending of apartheid, South African urban regions are still battling with an ongoing affordable housing crisis. Amidst growing critiques of the underutilisation of well-located state land, the Presidency acknowledges and intends to act on this through the accelerated release of public land to deliver more affordable housing opportunities in urban areas. However, within contemporary regulatory frameworks, urban practices around public land release have largely served short-term economic priorities through an emphasis on freehold disposal. This has resulted in a stagnant urban landscape with little room for urban land reform, perpetuated by a deterrence from state officials to engage in innovative practices around land release. Neglecting to understand the modalities and mechanisms around public land release for affordable housing has detrimental consequences for planning and human settlement development. This warrants a critical investigation into alternative mechanisms that present advantages for different circumstances. As such, the overall aim of this study is to understand the advantages of long-term leasehold arrangements in the delivery of well-located affordable housing as an additional mechanism for public land release. Methodologically, a Critical Discourse Analysis framework is used, supported by interviews and case examples, to answer the main and subsidiary research questions. The results of this study demonstrate the potential of long-term leasehold arrangements for the state and other affected stakeholders in the delivery and operation of affordable housing. These advantages yield long-term spatial transformative capacity that benefits all relevant stakeholders. Additionally, the results have highlighted the deficiencies in the regulatory systems for public land release and how this inhibits affordable housing objectives. Moving forward, the knowledge from this research will deepen the understanding of the relationship between planning and property systems. The study also informs key considerations regarding public land release and affordable housing. In this, it proposes legislative, policy and planning recommendations to facilitate effective long-term leasehold arrangements and holistic state property management.